Time and human fragility in the landscape similes of the Iliad - Bray, Chloe (The classical quarterly, 2022)
This article explores the propensity of Iliadic landscape similes to encourage reflections on human fragility. Landscape in the similes is usually interpreted as a medium which conveys a consistent symbolic value (for example storms as the hostility of nature); however, landscape is often a more flexible medium. By offering close readings of three Iliadic similes (winter torrents at 4.452-6, snowfall at 12.279-89 and clear night at 8.555-9), this article argues that landscape allowed the poet to frame the main narrative in various ways, both helping the listener to imagine described events and interrupting the listener's immersion in the main narrative. While many have analysed how similes offer analogies to the main narrative, the ways in which the same simile can also disrupt and reframe the narrative are less understood. This article observes that shifts in narrative space and time played a key role in changing the perspective of the listener. Taking a broadly phenomenological approach, it proposes that embodied descriptions of space, which recreate the experience of the moving body in landscape, invite the listener to consider the temporal scale of the natural world. By looking at how landscape in select similes shifts the listener's spatial and temporal experience, this article argues that landscape contributes to the wider Iliadic theme of human fragility. In particular, it identifies the potential for landscape similes to minimize the scale of human experience, question the possibility of human agency, and reveal the limitations of human perspectives and knowledge.
Gesehen am 24.06.2024